Pengaruh Literasi Perpajakan, Subjective Norms, dan Self Efficacy terhadap Minat Berkarier sebagai Konsultan Pajak pada Mahasiswa Akuntansi Generasi Z : Studi Pada Mahasiswa Akuntansi di Kota Serang - Fatiya Nuraini; Mochamad Fahru Komarudin; Novi Handayani (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This research is motivated by the implementation of the tax system harmonization policy aimed at optimizing tax ratio achievements to support financial stability amidst fluctuations in Gross Domestic Product (GDP) growth. This phenomenon demands the fulfillment of competent taxation human resources, which has not been fully balanced by high interest among accounting students in pursuing careers in this field. This study aims to determine and analyze the influence of Professional Training, Financial Rewards, and Work Environment on Career Interest in Taxation among Accounting Students in Serang City. The study employs an associative quantitative approach using a survey method involving 132 active undergraduate accounting students across Universitas Sultan Ageng Tirtayasa, Universitas Bina Bangsa, and Universitas Serang Raya. Data were analyzed using multiple linear regression with IBM SPSS Statistics Version 32. The results indicate that Professional Training, Financial Rewards, and Work Environment partially each have a positive and significant effect on Career Interest. Simultaneously, all three variables significantly influence students' Career Interest in taxation. Technical competence readiness through training, adequate material compensation expectations, and a supportive work environment are essential factors driving student career choices.